Перспективи інтеграції іноземної мови у процес вивчення дисциплін «Технологія конструкційних матеріалів» та «Матеріалознавство» - Колодій, Олександр Сергійович; Колодий, Александр Сергеевич; Kolodii, Oleksandr; Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна; Lemeshchenko-Lahoda, Viktoriia (ТДАТУ, 2021)
The main criterion for the effectiveness of higher education is the high level of specialists training. Its quality must meet the requirements set out in the State Educational Standards and labor market requirements. A modern engineer must be aware of comprehensive information on a wide range of issues in various fields of science and technology; his knowledge must be fundamental, practical and professionally oriented. The Language Integrated Learning helps to obtain all mentioned skills and contribute to the formation of students' knowledge that will have practical value in future professional activities.
Keywords: foreign language; Language Integrated Learning; Construction material technology; Materials technology